2018
DOI: 10.1002/ejoc.201800582
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated 1,2,3‐ and 1,2,4‐Triazolium Ionic Liquids

Abstract: Dialkyl triazolium triflimides with perfluorinated side chains were prepared as hydrophobic ionic liquids (ILs) for surface impregnation. The key feature of the new materials are relatively short perfluorohexyl residues (nC6F13 = RF) as the fluorinated part of the cations, making the target compounds beneficial alternatives to established products because of their enhanced degradability and therefore lower bioaccumulativity. As heterocyclic scaffold, either 1,2,3‐triazole or 1,2,4‐triazole were chosen. As the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Microcrystalline cellulose with a particle size of 20 µm and a molar mass of 37 kg mol −1 (as determined by viscosimetry) was purchased from Sigma Aldrich. [24] and ethyl bromide [19]. 1,2,3Triazole (0.22 mol) was dissolved in a suspension of potassium carbonate (0.43 mol) in 150 mL THF.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microcrystalline cellulose with a particle size of 20 µm and a molar mass of 37 kg mol −1 (as determined by viscosimetry) was purchased from Sigma Aldrich. [24] and ethyl bromide [19]. 1,2,3Triazole (0.22 mol) was dissolved in a suspension of potassium carbonate (0.43 mol) in 150 mL THF.…”
Section: Methodsmentioning
confidence: 99%
“…1-ethyl-3-methyltriazolium benzoate [EMTr][OBz] and 1-ethyl-3-methyltriazolium salicylate [EMTr][OSc] were prepared from 1-ethyl-3-methyl-1,2,3-triazolium bromide ([EMTr][Br]). The synthesis involved an alkylation with methyl iodide [ 24 ] and ethyl bromide [ 19 ]. 1,2,3Triazole (0.22 mol) was dissolved in a suspension of potassium carbonate (0.43 mol) in 150 mL THF.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These have been attached to imidazolium and triazolium cations. [23,24] FC-ILs with more than one fluorinated alkyl group are only known for classes II 2 [10,16,25,26] (imidazolium, triazolium, pyridinium, ammonium and phosphonium) and II 3 (phosphonium). [27] Alpers et al also reported some dicationic diammonium and diphosphonium ILs with two fluorinated alkyl groups.…”
Section: Introductionmentioning
confidence: 99%